STRATEGY FOR DEVELOPING UNDERSTANDING OF RELIGIOUS MODERATION IN THE MADRASAH CURRICULUM - Romlah, Listiyani Siti; Hasanah, Uswatun; Alhafiz, Farell; Purnama, Rahmad; Z, Wan Jamaluddin (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The pluralistic condition of Indonesia must be addressed wisely by all Indonesian people. Several study results show a high level of radicalism among students. Religious moderation can also be interpreted as an attitude to maintain balance and harmony amidst differences. The development of religious moderation, especially in madrasah, can be done in various ways. This research aims to examine further strategies for developing understanding of religious moderation in the madrasah curriculum. The approach used in this research is descriptive qualitative. This research uses field research. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis techniques used are data reduction, data presentation, as well as drawing conclusions and verification. ‎ The subjects of this research are those who are fully involved and integrated in the field, and have sufficient time to provide information. So, the subjects in this research were the Deputy Head of Curriculum, Worship Guide, and Islamic jurisprudence teacher at MTsN 2 South Lampung. The results of this research are that understanding of religious moderation can be developed through several strategies, one of which is recitation activities, express Islamic boarding schools, the love of orphanages, and internalization in the learning process.